Assessing the Effect of Riming on Snow Microphysics: The First Observational Study in East China. Issue 7 (5th April 2021) - Zhang, Yun; Zheng, Hepeng; Zhang, Lifeng; Huang, Yanbin; Liu, Xichuan; Wu, Zuhang
Abstract: Through the collision and freezing of supercooled droplets on the surface of snow particles, riming can change the density, fall velocity and aspect ratio of snow particles. Riming plays an important role in the formation of precipitation in cold clouds. To our knowledge, the impact of riming on snow microphysics is yet well understood, and there is a lack of observations obtained in China addressing this issue. For the first time in East China, the connection between riming and snow microphysical properties was investigated quantitatively during snow events in two winters. To quantify the degree of riming, the rime mass fraction (FR) is derived using the combination of a 2‐D video disdrometer (2DVD) and a weighing gauge. FR is added to the density‐diameter and fall velocity‐diameter relations, and a quantitative relation between riming and shapes of snowflakes is established based on the in situ observation of the 2DVD. The results show that riming can well explain the variability in the density and fall velocity of snowflakes. The changes in the shape of snowflakes can be divided into two distinct stages with increasing riming: in the initial stage (FR < 0.5), the aspect ratio increases very slowly, while in the later stage (FR > 0.5), the aspect ratio increases rapidly. Direct observations of the continuous changes in the shapes of snowflakes with riming are in good agreement with the retrieval results of radar. Key Points: The impact of riming on snow microphysical properties is reported for the first time in East China A quantitative relation between riming and the shapes of snowflakes is established based on in situ observations with a 2‐D video disdrometer The changes in the shapes of snowflakes can be divided into two distinct stages as riming progresses